Reflexões de História ambiental em Marajó de Dalcídio Jurandir: olhares e sentidos sobre a natureza - SANTOS, Paulo Henrique Santos dos (2021)
This work analyzes the relations between the human beings, nature and the past, based on Dalcídio Jurandir’s romance Marajó (1947), under an environmental history perspective. We established dialogues between literature and historiography to demonstrate a magnification of the comprehension of the problems caused by social inequality found mainly in the cities of Ponta de Pedras and Cachoeira do Arari in the brazilian sate of Pará in the first half of the 20th. We highlight the harmful permanence of historically constructed structures over time in this Society. We demonstrated the different relationships between opressed social groups and the Earth, the active presence of non human animals that exert influence in the local dynamics and the subversion of a literary tradition in which nature was represented in na abundant and harmonic form, giving way to the complaints of environmental degradation related to the exploitation made by the great farm owners.